Mutación r30q en cyp51a de neocosmospora solani asociada a resistencia a azoles (2021)
Neocosmospora and Fusarium are the etiological agents of human fusariosis such as onychomycosis, fungal keratitis and disseminated infections, and the most widely reported species are Neocosmospora keratoplastica, Neocosmospora falciformis and Fusarium oxysporum. In addition, they are resistance to azole compounds. Resistance to azoles has been mainly associated with mutations of the CYP51A gene. Additionally, other mechanisms have been determined such as mutations in the erg5 and erg3 genes in Candida or mutations in hmg1 and hapE in Aspergillus fumigatus. In Neocosmospora and F. oxysporum, the expression of different genes in response to azoles has been mainly evaluated; and CYP51A mutations in Neocosmospora keratoplastica. However, it is unknown whether resistance is associated with other mechanisms in Neocosmospora solani and F. oxysporum. Therefore, the objective of this study is to understand the mechanisms of resistance to azoles, by analyzing the genes CYP51A, erg3, erg5, hmg1 and hap5 in N. solani FMR 4391 and F. oxysporum FMR 9788. By means of the protocol of Calling variants gatk for RNA-seq and the libraries obtained by Castillo et al. (2020), variant verification was performed. It was found that there were no variants related to azole resistance in erg3, erg5, hmg1 and hap5. In addition, the R30Q mutation in N. solani CYP51A is reported and proposed as a mechanism of resistance to azoles, and the amino acid L218, which has been previously associated with resistance to posaconazole and itraconazole, is reported. In conclusion, the R30Q mutation is proposed as a mechanism of resistance to azoles in N. solani, however more studies are needed to confirm its relevance in resistance.